Models for the Observable System Parameters of Ultraluminous X-ray Sources - Madhusudhan, N; Rappaport, S; Podsiadlowski, P; Nelson, L (IOP Publishing, 2008)
We investigate the evolution of the properties of model populations of ultraluminous X-ray sources (ULXs) consisting of a black-hole accretor in a binary with a donor star. We have computed models corresponding to three different populations of black-hole binaries; two invoke stellar-mass (~10 Msun) black hole accretors, and the third utilizes intermediate-mass (~1000 Msun) black holes (IMBHs). For each of the three populations, we computed 30,000 binary evolution sequences using a full Henyey stellar evolution code. The optical flux from the model ULXs includes contributions from the accretion disk, due to x-ray irradiation as well as intrinsic viscous heating, and that due to the donor star. We present "probability images" for the ULX systems in planes of color-magnitude, orbital period vs. X-ray luminosity, and luminosity vs. evolution time. Estimates of the numbers of ULXs in a typical galaxy as functions of time and of X-ray luminosity are also presented. Our model CMDs are compared with six ULX counterparts that have been discussed in the literature. Overall, the observed systems seem more closely related to model systems with very high-mass donors (> ~25 Msun) in binaries with IMBH accretors. However, significant difficulties remain with both the IMBH and stellar-mass black hole models.